Global warming, technological change and trade in carbon energy: Challenge or threat? - Gunter Stephan; Georg Müller-Fürstenberger (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Is it possible to combat global climate change through North-to-South technology transfer even without a global climate treaty? Or do carbon leakage and the rebound effect imply that it is possible to take advantage of technological improvements under the umbrella of a global arrangement only? For answering these questions two possible states of the world are discussed: one, where more energy efficient technologies are transferred unconditionally from the North to the South, and where regions do not cooperate in the solution of the global climate problem but unilaterally decide on climate policies and technology transfers; one, where the North-to-South technology transfer is tied to the requirement that the South in some way contributes to the solution of the global climate problem. Rebound and leakage effects hinder a sustainable and welfare improving solution of the climate problem.
Keywords: C68; D58; F18; Q56; Q54; 330; global warming; climate change; technological change; technology transfer; trade in carbon energy; Post-Kyoto-policy regimes